1993
DOI: 10.1254/jjp.62.231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of κ-Agonist on the Antinociception and Locomotor EnhancingAction Induced by Morphine in Mice

Abstract: ABSTRACT-We examined the effects of IV°-nitro-L-arginine (L-NNA) on isolated rabbit afferent arterioles to confirm that nitric oxide is released at the resistance vessel level in the kidney. We microdissected the superficial afferent arterioles from the kidneys of New Zealand White rabbits. Each afferent arteriole was cannulated with a micropipette system, and the intraluminal pressure was set at 80 mmHg. By our methods, we found that norepinephrine (NE) decreased the lumen diameter of the afferent arterioles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…In the kidney, NO has numerous important functions in the control of renal hemodynamics and excretory function (22,26,34). It is also well known that chronic blockade with the NOS inhibitor L-NAME results in hypertension and renal glomerular injury (3,37).…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, NO has numerous important functions in the control of renal hemodynamics and excretory function (22,26,34). It is also well known that chronic blockade with the NOS inhibitor L-NAME results in hypertension and renal glomerular injury (3,37).…”
Section: Discussionmentioning
confidence: 99%
“…However, interestingly, Toda et al (20,26) reported that Ang II caused relaxation in the helically cut strip of dog renal artery, and this relax ation was mediated by vasodilatory PGs. In fact, isolated AA has the ability to produce vasodilatory PGs (21) and NO (12). Then, we hypothesized that vasodilatory PGs and NO counteract the vasoconstrictor effect of Ang II on the isolated AA.…”
Section: Discussionmentioning
confidence: 97%
“…Ito et al (13) report ed that Ang II caused segmental constrictions and the strongest was observed in the segment close to the glo merulus using microperfused AA. While Ito et al isolated the AA with glomerulus, we isolated only the AA in our preparation (12), and both ends of the AA were cannulat ed with a pipette system (Figs. 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations